The Structure of Drymonims in Radviliškis District - Mickienė, Ilona; Bieliauskaitė, Rimantė (Respectus Philologicus, 2018)
This article analyses the drymonyms from the “Lithuanian Forests Name Book”, Lithuanian Geoinformation Data Base and Radviliškis district map (200). Drymonyms are a constantly changing part of the Lithuanian landscape, and it is imperative to fix and research them periodically. Drymonyms in Radviliškis district have not been researched in any way. The classification of Radviliškis district drymonyms, classifying primary and secondary drymonyms first, is based on grammatical-structural classification scheme of Aleksandras Vanagas. Secondly, drymonyms with suffixes or inflections were selected as well as mixed structure drymonyms, compound and composite drymonyms. The research demonstrated that the majority of Radviliškis district drymonyms were identified as secondary names (88.5%), whereas the number of primarily names was significantly lower (11.5%). The analysis of Radviliškis district drymonyms will be useful for further research of this region’s toponym classification. Investigation of the drymonyms and understanding of their common word-building tendencies could lead to further research of extralinguistic aspects (social, economic and psycholinguistic) of the region’s toponyms.
Keywords: Drymonyms; Grammatical-Structural Classification; Primary and Secondary Names; Derivation Analysis